Butterflies of Quercus leucotrichophora - Cedrus deodara Forest - Singh, Arun P.; Singh, Raka (Indian Forester, 1998)
A study was carried out in a Quercus leucotrichophora - Cedrus deodara forest to find out its butterfly species composition. their status. habits. nectar plants. larval food plants and seasonal occurrence. The dominant flora of the study area was also recorded. A total 35 butterfly species were recorded. Field observation showed that all the species of butterflies are dependent for food and netltar on plants that are typical of Quercus leucotrichophora - Cedrus deodara forest ecosystem.